2021
DOI: 10.1302/2633-1462.28.bjo-2021-0126
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of retrieved STRYDE nails

Abstract: Aims The aim of this study was to present the first retrieval analysis findings of PRECICE STRYDE intermedullary nails removed from patients, providing useful information in the post-market surveillance of these recently introduced devices. Methods We collected ten nails removed from six patients, together with patient clinical data and plain radiograph imaging. We performed macro- and microscopic analysis of all surfaces and graded the presence of corrosion using validated semiquantitative scoring methods. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…A similar report by Frommer et al [ 20 ] identified osteolytic changes in 20 of the 57 (35%) implanted nails at a mean 9.5 months after index lengthening surgery. They also found macroscopic corrosion at the modular junction in 83% of recipients, similar to that reported by our group in a previous publication [ 19 ] and a separate analysis of retrieved nails at another institution [ 30 ]. In a comparative study of multiple variations of an intramedullary limb lengthening nail, Iobst et al [ 29 ] observed a greater proportion of bone abnormalities at the modular junction of the STRYDE nail, as compared to the PRECICE or FITBONE (Orthofix Medical Inc., Lewisville, TX, USA).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar report by Frommer et al [ 20 ] identified osteolytic changes in 20 of the 57 (35%) implanted nails at a mean 9.5 months after index lengthening surgery. They also found macroscopic corrosion at the modular junction in 83% of recipients, similar to that reported by our group in a previous publication [ 19 ] and a separate analysis of retrieved nails at another institution [ 30 ]. In a comparative study of multiple variations of an intramedullary limb lengthening nail, Iobst et al [ 29 ] observed a greater proportion of bone abnormalities at the modular junction of the STRYDE nail, as compared to the PRECICE or FITBONE (Orthofix Medical Inc., Lewisville, TX, USA).…”
Section: Discussionsupporting
confidence: 87%
“…Since a manufacturer recall in early 2021, multiple reports have demonstrated the presence of adverse tissue reactions in stainless-steel intramedullary lengthening nails [ 19 , 20 , 21 , 22 , 23 , 24 , 29 , 30 ]. In a report of three cases, Sax et al [ 19 ] demonstrated radiographic osteolysis in patients implanted with the stainless-steel nail with histologic confirmation of phagocytic activity of green-gold crystalline debris characteristic of metal debris.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the observations of Iobst et al 15 who believed the finding to be STRYDE-specific, and one could speculate that mechanically assisted corrosion at the bolts weakened the material and made them more susceptible to breakage under full load. 8,9,12,15 There was no relevant difference in terms of distraction and consolidation indices between the STRYDE and PRECICE cohort, in contrast to the results of Galal et al, 14 who reported a statistically significant lower distraction rate and a statistically significant higher bone healing index for their STRYDE compared to their PRECICE cohort. However, bone healing seemed to be affected in patients treated with the STRYDE nail in our cohort, since these patients were more likely to undergo revision surgery due to delayed consolidation in comparison to the PRECICE cohort.…”
Section: Discussionmentioning
confidence: 72%
“…However, they are limited in terms of comparability to other intramedullary lengthening systems. [8][9][10][11][12][13]15,21 This study was designed to provide a comprehensive approach in terms of clinical and radiological outcome of treatment with the conventional PRECICE and the STRYDE intramedullary lengthening nail. Compared to previous studies, a large and homogenous group of patients using a 2:1 matched-pair design was examined.…”
Section: Discussionmentioning
confidence: 99%
“…Fretting corrosion, or micromotion at the same site, as well as pitting corrosion have also been implicated. 7 , 12 , 15 , 18 However, further investigation regarding the incidence, consequence, and correction of this sequelae is needed.…”
Section: Discussionmentioning
confidence: 99%